IgG Binds Escherichia coli Serine Protease EspP and Protects Mice From E. coli O157:H7 Infection - Ashmita Tontanahal; Vanessa Sperandio; Olga Kovbasnjuk; Sebastian Loos; Ann-Charlotte Kristoffersson; Diana Karpman; Ida Arvidsson (Frontiers in Immunology, 2022)
Shiga toxin-producing Escherichia coli O157:H7 is a virulent strain causing severe gastrointestinal infection, hemolytic uremic syndrome and death. To date there are no specific therapies to reduce progression of disease. Here we investigated the effect of pooled immunoglobulins (IgG) on the course of disease in a mouse model of intragastric E. coli O157:H7 inoculation. Intraperitoneal administration of murine IgG on day 3, or both on day 3 and 6, post-inoculation improved survival and decreased intestinal and renal pathology. When given on both day 3 and 6 post-inoculation IgG treatment also improved kidney function in infected mice. Murine and human commercially available IgG preparations bound to proteins in culture filtrates from E. coli O157:H7. Bound proteins were extracted from membranes and peptide sequences were identified by mass spectrometry. The findings showed that murine and human IgG bound to E. coli extracellular serine protease P (EspP) in the culture filtrate, via the IgG Fc domain. These results were confirmed using purified recombinant EspP and comparing culture filtrates from the wild-type E. coli O157:H7 strain to a deletion mutant lacking espP. Culture filtrates from wild-type E. coli O157:H7 exhibited enzymatic activity, specifically associated with the presence of EspP and demonstrated as pepsin cleavage, which was reduced in the presence of murine and human IgG. EspP is a virulence factor previously shown to promote colonic cell injury and the uptake of Shiga toxin by intestinal cells. The results presented here suggest that IgG binds to EspP, blocks its enzymatic activity, and protects the host from E. coli O157:H7 infection, even when given post-inoculation.